Development of an Employee Attendance Management Information System Based on Web and Mobile with Location-Based Service - Aria Rizky Prasetyo; Ikrimach Ikrimach (Jurnal Improsci, 2025)
Background. Personnel attendance administration activities at the Karanganyar Regency Education and Culture Office have been integrated with the central system for civil servants, but the attendance method for non-civil servants is not available in a structured manner, so it risks reducing data integrity, being inaccurate, and not allowing real-time monitoring. Aims. This research aims to develop a web-based and mobile-based employee attendance management and scheduling application using Location Based Service in a case study at the Karanganyar Regency Education and Culture Office. Methods. The application that was built provides a presence feature based on the Global Positioning System and a camera for proof of presence photos. Location-based service is used to validate the location of employees when attending to match the predetermined work area. The system is designed using a client-server architecture with a Laravel-based web application for admins, a mobile application for employees, and a centralized database to facilitate data management. Result. The evaluation of the system's functionality is conducted using the black box testing method to assess the suitability of the output results for the specified use scenario. Conclusion. The test results indicate that all application functions meet user needs. Consequently, the developed system is expected to enhance efficiency, ensure data integrity, and offer a more modern and integrated presence solution in the administrative process of non-civil servant personnel within the Karanganyar Regency Education and Culture Office.